Absolute Pitch and Musical Expertise Modulate Neuro-Electric and Behavioral Responses in an Auditory Stroop Paradigm - Sharma, Vivek V.; Thaut, Michael; Russo, Frank; Alain, Claude (Frontiers in Neuroscience, 2019)
Musicians have considerable experience naming pitch-classes with verbal (e.g., Doh, Ré, Mi, etc.) and semiotic tags (e.g., musical notation, etc.). On one end of the spectrum, musicians can identify the pitch of a piano tone or quality of a chord without a reference tone (i.e., absolute pitch or relative pitch), which suggests strong associations between the perceived pitch information and verbal labels. Here, we examined the strength of this association using auditory versions of the Stroop task while neuro-electric brain activity was measured using high-density electroencephalography. In separate blocks of trials, participants were presented with congruent or incongruent auditory words from English language (standard auditory Stroop), Romanic solemnization or German key lexicons (the latter two versions require some knowledge of music notation). We hypothesized that musically trained groups would show greater Stroop interference effects when presented with incongruent musical notations than non-musicians. Analyses of behavioral data revealed small or even non-existent congruency effects in musicians for solfège and keycodes versions of the Stroop task. This finding was unexpected and appears inconsistent with the hypothesis that musical training and absolute pitch are associated with high strength response level associations between a perceived pitch and verbal label. The analyses of event-related potentials revealed three temporally distinct modulations associated with conflict processing. All three modulations were larger in the auditory word Stroop than in the other two versions of the Stroop task. Only absolute pitch musicians showed significant congruity effects around 450 ms and 750 ms post-stimulus when stimuli were presented as Germanic keycodes (i.e., C or G). This finding suggests absolute pitch possessors may process alpha-numeric encodings as word forms with a semantic value, unlike their relative pitch possessing counterparts and non-musically trained individuals. However, the strength of musical conditional associations may not exceed that of standard language in speech.